Irreversible plasma and muscle protein oxidation and physical exercise. (1st February 2019) - Gorini, Giulia; Gamberi, Tania; Fiaschi, Tania; Mannelli, Michele; Modesti, Alessandra; Magherini, Francesca
Abstract: The imbalance between the reactive oxygen (ROS) and nitrogen (RNS) species production and their handling by the antioxidant machinery (low molecular weight antioxidant molecules and antioxidant enzymes), also known as oxidative stress, is a condition caused by physiological and pathological processes. Moreover, oxidative stress may be due to an overproduction of free radicals during physical exercise. Excess of radical species leads to the modification of molecules, such as proteins – the most susceptible to oxidative modification – lipids and DNA. With regard to the oxidation of proteins, carbonylation is an oxidative modification that has been widely described. Several studies have detected changes in the total amount of protein carbonyls following different types of physical exercise, but only few of these identified the specific amino acidic residues targets of such oxidation. In this respect, proteomic approaches allow to identify the proteins susceptible to carbonylation and in many cases, it is also possible to identify the specific protein carbonylation sites. This review focuses on the role of protein oxidation, and specifically carbonyl formation, for plasma and skeletal muscle proteins, following different types of physical exercise performed at different intensities. Furthermore, we focused on the proteomic strategies used to identify the specific protein targets of carbonylation. Overall, our analysis suggests that regular physical activity promotes a protection against protein carbonylation, due to the activation of the antioxidant defence or of the turnover of protein carbonyls. However, we can conclude that from the comprehensive bibliography analysed, there is no clearly defined specific physiological role about this post-translational modification of proteins.